Burger Model And Analytic Conditional Approach (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper the range of (x,t) for the corresponding u involved in Burger’s equation is obtained. The used methodology is C-R equation along with conditions   u_x=v_t,   u_t=-v_x. When approached through this method easily we can solve  v for the given  u and  u  for the given  v simultaneously without loss of generality.